Polymer lipid hybrid nanoparticles for phytochemical delivery: challenges, progress, and future prospects - Iqra Rahat; Pooja Yadav; Aditi Singhal; Mohammad Fareed; Jaganathan Raja Purushothaman; Mohammed Aslam; Raju Balaji; Sonali Patil-Shinde; Md. Rizwanullah (Beilstein Journal of Nanotechnology)
Phytochemicals, naturally occurring compounds in plants, possess a wide range of therapeutic properties, including antioxidant, anti-inflammatory, anticancer, and antimicrobial activities. However, their clinical application is often hindered by poor water solubility, low bioavailability, rapid metabolism, and instability under physiological conditions. Polymer lipid hybrid nanoparticles (PLHNPs) have emerged as a novel delivery system that combines the advantages of both polymeric and lipid-based nanoparticles to overcome these challenges. This review explores the potential of PLHNPs to enhance the delivery and efficacy of phytochemicals for biomedical applications. We discuss the obstacles in the conventional delivery of phytochemicals, the fundamental architecture of PLHNPs, and the types of PLHNPs, highlighting their ability to improve encapsulation efficiency, stability, and controlled release of the encapsulated phytochemicals. In addition, the surface modification strategies to improve overall therapeutic efficacy by site-specific delivery of encapsulated phytochemicals are also discussed. Furthermore, we extensively discuss the preclinical studies on phytochemical encapsulated PLHNPs for the management of different diseases. Additionally, we explore the challenges ahead and prospects of PLHNPs regarding their widespread use in clinical settings. Overall, PLHNPs hold strong potential for the effective delivery of phytochemicals for biomedical applications. As per the findings from pre-clinical studies, this may offer a promising strategy for managing various diseases.